Interview with independent dance artist Cecilia Macfarlane. (1st June 2015) - Meehan, Emma; Macfarlane, Cecilia
In this interview, independent dancer Cecilia Macfarlane talks about her project with the Japanese Contemporary Dance Network (JCDN) in 2013. To date, Macfarlane has undertaken eight trips to Japan, primarily to introduce her community dance practice to Japanese artists. However, during her visit in 2013, she was invited to learn folk dances from the north-east of Japan, in the Tohoku region most affected by the earthquake and tsunami in 2011. The interview is movingly interwoven with Macfarlane's experience of losing her son. The sudden devastation following his death is described by Macfarlane as a 'personal tsunami', which is discussed alongside the loss and destruction wrought in Japan by earthquake, tsunami and nuclear devastation. In this way, autobiographical material is brought to bear on understanding the experiences of the survivors and to contribute to the development of Macfarlane's artistic process alongside the project.